Power Analysis for Real-Time PCR Quantification of Genes in Activated Sludge and Analysis of the Variability Introduced by DNA Extraction - Dionisi, Hebe M. (American Society for Microbiology, 2003)
The aims of this study were to determine the power of discrimination of the real-time PCR assay for monitoring fluctuations in microbial populations within activated sludge and to identify sample processing points where methodological changes are needed to minimize the variability in target quantification. DNA was extracted using a commercially available kit from mixed liquor samples taken from the aeration tank of four bench-scale activated-sludge reactors operating at 2-, 5-, 10-, and 20-day solid retention times, with mixed-liquor volatile suspended solid (MLVSS) values ranging from 260 to 2,610 mg/liter. Real-time PCR assays for bacterial and Nitrospira 16S rRNA genes were chosen because they represent, respectively, a highly abundant and a less-abundant bacterial target subject to clustering within the activated sludge matrix. The mean coefficient of variation in DNA yields (measured as microgram of DNA per milligram of MLVSS) in triplicate extractions of 12 different samples was 12.2%. Based on power analyses, the variability associated with DNA extraction had a small impact on the overall variability of the real-time PCR assay. Instead, a larger variability was associated with the PCR assay. The less-abundant target (Nitrospira 16S rRNA gene) had more variability than the highly abundant target (bacterial 16S rRNA gene), and samples from the lower-biomass reactors had more variability than samples from the higher-biomass reactors. Power analysis of real-time PCR assays indicated that three to five samples were necessary to detect a twofold increase in bacterial 16S rRNA genes, whereas three to five samples were required to detect a fivefold increase in Nitrospira 16S rRNA genes.